Manajemen Islamic Culture Melalui Pembiasaan Sholat Dhuha Berjamaah dalam Meningkatkan Karakter Kedisiplinan Siswa - Cindy Mistiningsih; Eni Fariyatu Fahyuni (Manajemen Pendidikan Islam STIT Palapa Nusantara, 2020)
This paper discusses the management of Islamic Cultur through habituating Dhuha Prayers in Improving Student Discipline. Islamic Cultur is a practice of habituating Islamic values, one of which is the implementation of habituation in congregation. This culture is implemented and familiarized in order to improve student discipline. Prayer is a compulsory worship that must be performed by every Muslim. Prayer services will be able to keep the culprit from the heinous and unjust practices. Prayer is one of the worship services that has disciplinary implications for the culprit. This research belongs to the type of qualitative-descriptive research that is expected to be able to uncover various information with a careful and meaningful description-analysis. Sources of data in this study include the principal, student staff and staff and teachers of Islam. Data collection is done by interview, observation, and documentation. As for the data analysis techniques through the stages of data reduction, data presentation and data analysis. The results of this research are (1) Management of Islamic Cultur held through habituation of Dhuha Berma’ah (2) Habituation of Dhuha prayer in congregation can improve student discipline.